Modern Analytical Facilities 2. A Review of Quality Assurance and Quality Control (QA/QC) Procedures for Lithogeochemical Data - Piercey, Stephen J. (Geoscience Canada, 2014)
Quality assurance and quality control (QA/QC) are critical components of modern analytical geochemistry. A properly constructed QA/QC program identifies both the source of analytical error and provides a means of establishing confidence in and assessing limitations of analytical data. A QA/QC program involves monitoring precision, accuracy, and potential contamination from sampling to analysis. Precision can be monitored via the systematic insertion of sample, pulp, and analytical duplicates, and reference materials; the resulting data are subsequently evaluated using scatterplots, statistical tests (e.g. % relative standard deviation), Thompson-Howarth plots, and the average coefficient of variation (CVavg (%)). Accuracy is determined through the submission of reference materials and monitored using statistical tests (e.g. % relative difference, t-test) and Shewart control charts. Blanks test contamination and results are monitored using Shewart control charts. SOMMAIRE L’assurance de la qualité et le contrôle de la qualité (AQ-CQ) sont deux composantes essentielles à la géochimie analytique moderne. Un programme AQ-CQ bien conçu défini à la fois la source de l’erreur d’analyse et un moyen d’établir la confiance et d’évaluer les limites des données analytiques. Un programme AQ-CQ comprend le contrôle de la précision, de l’exactitude et de la contamination potentielle, de l’étape d’échantillonnage à l’analyse. La précision peut être contrôlée via l’insertion systématique d’échantillon, de pulpes, et de doublons d’analyse, et de matériaux de référence; les données obtenues sont ensuite évaluées en utilisant des diagrammes de dispersion, des tests statistiques (pourcentage d’écart type relatif, par ex.), des courbes de Thompson-Howarth, et des coefficients de variation moyens (CVm %). La précision est déterminée par la soumission de documents de référence et de contrôle par des tests statistiques (différence relative en %, t-test, par ex.) et des graphiques de contrôle de Shewhart. La contamination d’essais à blanc et les résultats sont contrôlés par des graphiques de contrôle Shewhart.